Fluid intake and recommendations in older adults: More data are needed. Issue 2 (June 2016) - Scherer, R.; Maroto‐Sánchez, B.; Palacios, G.; González‐Gross, M.
Abstract: Older people are vulnerable to hypohydration due to physiological and cognitive changes that occur with age. Inadequate fluid intake is the main contributor to hypohydration in this age group, but very little is known about their drinking habits and specific fluid intake recommendations are lacking. Therefore, the aim of this short review was to summarise published data on fluid consumption in adults aged 65 years and older. The PubMed database was searched for all relevant studies published between 1995 and 2014 globally. The search identified 12 suitable papers for review. Results indicated that reported fluid intake in older adults varied considerably between studies. Lack of standardisation for reporting 'fluid intake' is a problem in this literature. In conclusion, data about fluid intake in older adults are scarce and inconclusive. Consensus on a definition for 'fluid intake' is necessary if an international age‐specific reference range for the elderly is to be set.